Hubungan Peran Orang Tua Dalam Pendidikan Kesehatan Reproduksi Dengan Kesiapan Menghadapi Menarche Remaja Putri Di Sdn 66 Kota Bengkulu - Cindy Afrianis; Danur Azissah; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Puberty in adolescent girls is marked by menarche, which is the first menstruation that occurs due to the shedding of the endometrial layer containing many blood vessels in the uterus. Based on the researcher's initial survey of several parents of adolescent girls at SDN 66 Bengkulu City, it was found that most parents did not fully understand the importance of early reproductive health education. The purpose of this study was to determine the relationship between the role of parents in reproductive health education and the readiness of adolescent girls at SDN 66 Kota Bengkulu to face menarche. This study used a quantitative descriptive method for a cross-sectional research design. The population in this study consisted of 59 female adolescents in grades 4 and 5 at SDN 66 Bengkulu City. The sample consisted of 36 female adolescents. Data collection was carried out by distributing questionnaires. Bivariate analysis used the chi-square statistical test. Most parents of adolescent girls at SDN 66 Bengkulu City played a positive role in reproductive health education, namely 55.6%. And most adolescent girls at SDN 66 Bengkulu City, namely 66.7%, showed readiness to face menarche. The results of the chi-square test showed a p-value of 0.000 (< 0.05). It is recommended that parents, schools, and adolescent girls play an active role in reproductive health education from an early age through positive communication and reliable sources of information. Furthermore, it is hoped that future researchers will develop this study with a broader scope and more diverse variables.